How Does the Changing Access to Resources Affect the Power and Authority of the Postsocialist Romanian State? - Epure, Madalina (Journal of Economic Development, Environment and People, 2013)
In the past two decades, former postsocialist countries such as Romania have experienced very radical changes in terms of government and resource policy (Swinnen, 1997; Swinnen et al., 1997; Szelenyi, 1998; Turnock, 1998). To make sense of these changes this review paper will make use of recent postsocialist literature, which links the access and control over resources to the exercise of power and authority in the postsocialist state (Berry, 1993; Lund, 2002; Verdery, 2002; Ribot and Peluso, 2003; Sikor, 2006; Sikor and Lund, 2009; Sikor, Stahl and Dorondel, 2009). The review paper aims to re-trace this line in postsocialist thinking in the relevant literature and show how the concepts of property and access to resources are connected to the crucial concepts of power and authority. It will perform a critical review of the relevant literature and also explore the aforementioned concepts of property, access, power, authority and state. It will furthermore show how these concepts feed into the formation and consolidation of the Romanian postsocialist state. Since conflicts over property are emphasised by postsocialist researchers (de Waal, 1996; Giordano and Kostova, 1996; Verdery, 1999; Rabinowicz and Swinnen, 1997; Swinnen and Mathjs, 1997; Szelenyi, 1998; Sikor, 2003; Sikor, Stahl and Dorondel, 2009; Dorondel and Sikor, 2009), these are underlined here and thought to be the main thread connecting property and access to resources with power and authority in the new state. More specifically, the paper will reveal how said conflicts force actors to seek the authorization of their property claims at the door of the state. By doing so, they grant the new state the authority to do so again in the future and thereby contribute to the consolidation of its legitimacy. Essentially this review paper argues that changes to resource access engender conflicts, which in turn lead to the formation of a new social contract between the postsocialist state and its people (Lund, 2002).